PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2022 - Aisyah, Inasha Nur; Isnawati, Isnawati (SINERGI : Jurnal Riset Ilmiah, 2025)
This research aims to analyze the effect of Corporate Social Responsibility on Financial Performance in Banking Companies listed on the Indonesia Stock Exchange for the period 2020-2022. The independent variable used in this study is Corporate Social Responsibility. And the dependent variable used is financial performance proxied by ROA and ROE. The population of this study was 46 banking companies and sample selection using purposive sampling with a total of 22 companies. This study uses a quantitative descriptive method using secondary data in the form of annual reports and sustainability reports of banking companies in 2020-2022. The data is processed using the panel data regression analysis method using the Eviews version 12 program. The results of this study prove that Corporate Social Responsibility affects financial performance.